2002
DOI: 10.1002/hyp.1071
|View full text |Cite
|
Sign up to set email alerts
|

A new interpretation of kinematic stormflow generation

Abstract: Abstract:The paper reviews a number of possible fast and slow hydrological flow mechanisms to account for rapid runoff generation within a catchment. A new interpretation of the kinematic wave process is proposed which develops some of these concepts to explain rapid subsurface flow from a watershed. Evidence for the process is provided by the results from a laboratory soil core experiment and an investigation of the hydrology of a Dartmoor hillslope. A tension response was monitored in the soil core in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 30 publications
2
37
1
Order By: Relevance
“…Movement through macropores may result in transport of herbicides to impermeable layers (bedrock, etc.) where they move along those impermeable layers to streams (Williams et al, 2002;Buttle and McDonald, 2002).…”
Section: Stream Contamination During Application and Storm Runoffmentioning
confidence: 99%
“…Movement through macropores may result in transport of herbicides to impermeable layers (bedrock, etc.) where they move along those impermeable layers to streams (Williams et al, 2002;Buttle and McDonald, 2002).…”
Section: Stream Contamination During Application and Storm Runoffmentioning
confidence: 99%
“…Studies have found different controls on how stored water travels rapidly to the stream: transmissivity feedback (Kendall et al, 1999;Bishop, 1991), macropore flow (McDonnell, 1990), pressure wave propagation (Torres et al, 1998;Williams et al, 2002) and hydrodynamic mixing (Jones et al, 2006). However, open questions remain in quantifying the difference between celerity and velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Macropore flow of old water has been observed for over 20 yr now (McDonnell, 1990) but there is still much ongoing discussion regarding whether this rapid effusion of old, pre-event water, is indeed preferential flow or pressure wave displacement (Torres et al, 1998;Williams et al, 2002) or some combination of both. These questions lie at the heart of the double paradox, as outlined by Kirchner (2003) and tested by Bishop et al (2004), and quantification of flow and transport processes that connect the plot, hillslope and catchment scales.…”
Section: Introductionmentioning
confidence: 99%